Peran Branding dan Digitalisasi dalam Pengembangan UMKM Jamu di Desa Balai Kasih Melalui Program KKN UINSU 2025 - Habibi, Setioga Mulya; Ansari, Nazwa; Putra, Afryan Syah; Harahap, Karina Azzahra; Hayati, Amal (Pusdikra Publishing, 2025)
Digital technology development has not been fully utilized by rural MSMEs, including Jamu Asli Nek Poniyem in Balai Kasih Village, which lacked business identity and digital connectivity. This condition caused low visibility and limited market reach. This study aims to strengthen MSME branding and digitalization through the KKN UINSU 2025 program. The method used was a participatory approach involving observation, interviews, socialization, mentoring, and literature study. The activities included creating business banners as visual identity and registering the business location on Google Maps. The results show that the MSME gained a clearer business identity, became easier to recognize by the community, and its location could be accessed online. In addition, the business owner’s understanding and confidence in using digital technology increased. This simple digitalization approach proved effective in improving visibility, consumer access, and development opportunities for rural MSMEs.